(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aimed to investigate the impact of intellectual capital, represented by its dimensions of human capital, relational capital, and structural capital, on enhancing production flexibility with its various dimensions, including machine flexibility, new product introduction flexibility, and human resource flexibility, through an applied study at Dubai Pharmaceutical Industries Company. The main objective of the study was to analyze the nature of the relationship between intellectual capital and the organization’s ability to adapt to operational and production changes, as well as to determine the extent to which each dimension of intellectual capital contributes to enhancing production flexibility within the company. The descriptive analytical approach was adopted because it is suitable for the nature and objectives of the research. This approach helps in describing phenomena and analyzing relationships among variables scientifically and systematically. The study population included all employees working at Dubai Pharmaceutical Industries Company located in Samarra, Salah Al-Din Governorate, Iraq - a total of (101) employees. Since this is a relatively small study population, the comprehensive survey method (Census Method) was used to represent fully all members of the population and achieve more accuracy in results. However, (22) questionnaires were excluded due to incomplete data or inconsistencies that would affect the validity of statistical analysis. Therefore, valid questionnaires for analysis came down to (79), with a response rate of 78.2%. The results of the study showed a statistically significant positive effect of intellectual capital on production flexibility at the significance level (α ≤ 0.05). Results also indicated that intellectual capital has a significant effect on all dimensions of production flexibility, i.e., machine flexibility, new product introduction flexibility, and human resource flexibility.